2009
DOI: 10.1016/j.bbrc.2009.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of αII spectrin in normal human cells by siRNA leads to chromosomal instability and decreased DNA interstrand cross-link repair

Abstract: Nonerythroid α-spectrin (αIISp) is a structural protein involved in repair of DNA interstrand crosslinks and is deficient in cells from patients with Fanconi anemia (FA), which are defective in ability to repair cross-links. In order to further demonstrate the importance of the role that αIISp plays in normal human cells and in the repair defect in FA, αIISp was knocked down in normal cells using siRNA. Depletion of αIISp in normal cells by siRNA resulted in chromosomal instability and cellular hypersensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(140 citation statements)
references
References 23 publications
8
132
0
Order By: Relevance
“…However, studies have shown that protection or recovery of α-II spectrin is correlated to neuronal survival 43 . Spectrin is also involved in repairing DNA damage 44 , a process which occurs in TBI 45,46 . Perhaps the increase in α-II spectrin 7 d after injury is an indicator of spontaneous repair.…”
Section: Brain Tissue Break-down Products Indicate Persistent Proteolmentioning
confidence: 99%
“…However, studies have shown that protection or recovery of α-II spectrin is correlated to neuronal survival 43 . Spectrin is also involved in repairing DNA damage 44 , a process which occurs in TBI 45,46 . Perhaps the increase in α-II spectrin 7 d after injury is an indicator of spontaneous repair.…”
Section: Brain Tissue Break-down Products Indicate Persistent Proteolmentioning
confidence: 99%
“…Previous reports of siRNA knockdown suggest that complete knockdown of aII-spectrin is lethal to cells. 19 We used antibiotic selection to maintain the aII-spectrin reduced phenotype and prevent the overgrowth of untransfected cells.…”
Section: Reduced Expression Of Aii-spectrinmentioning
confidence: 99%
“…Additionally, aIISp colocalizes with FANCA and XPF forming discrete foci in response to 8-MOP plus UVA light, indicating a possible functional link between these proteins in response to ICL damage [Sridharan et al, 2003]. Knockdown of aIISp resulted in formation of fewer nuclear foci following treatment with MMC as well as decreased survival, further implicating this protein in ICL recognition [McMahon et al, 2009]. A consequence of this damage recognition is recruitment of repair proteins including ERCC1-XPF to the site of DNA damage in preparation for the next step of the repair process.…”
Section: Icl Recognitionmentioning
confidence: 90%